Geosynthetic-Reinforced Soil Retaining Walls as Important Permanent Structures 1996 - 1997 Mercer Lecture. Issue 2 (1997) - Tatsuoka, F.; Tateyama, M.; Uchimura, T.; Koseki, J.
Abstract : During the past decade, more than 26 km of geosynthetic-reinforced soil retaining walls (GRS-RWs) with full-height rigid (FHR) facings were constructed in Japan as important permanent structures mainly for railways and occasionally for highways. These include retaining walls for embankments, bridge abutments, a wall backfilled with a nearly saturated clay constructed on a thick soft clay deposit, a wall that survived a very severe earthquake, and walls constructed to support bullet train tracks. The full-height rigid facings are cast in place using staged construction procedures. A new method of stiffening reinforced soil by vertical preloading and prestressing is also described.